THE EFFECT OF WORK ENVIRONMENT AND WORK MOTIVATION ON EMPLOYEES PERFORMANCE OF EMPLOYEES COOPERATIVE TELKOM SAMARINDA - Ris Setyawati; Vera Anitra; Mursidah Nurfadillah; Joko Sabtohadi (Jurnal Scientia, 2022)
This research aims to see how the work environment and motivation affect the performance of the Telkom Samarinda Employee Cooperative. This study uses a quantitative approach with data collection methods using a Likert scale instrument through a questionnaire distributed via a google form. Correspondents in this study were Telkom Samarinda Employee Cooperative employees, as many as 100 people. This study uses SPSS 25.0, and the calculation uses the solving formula. The results of the study indicate that the work environment has a positive but not significant effect on the performance of the Telkom Samarinda Employee Cooperative employees, meaning that based on the existing indicators, lighting and air circulation have not provided a comfortable and conducive feeling. In contrast, the influence of work motivation on employee performance has a positive and significant effect on the performance of employees of the Telkom Samarinda Employee Cooperative.